EDUKASI KESEHATAN ALAT REPRODUKSI MENGGUNAKAN MEDIA PAKEM BRAILLE DI MTS YAKETUNIS YOGYAKARTA - Novia Indah Permatasari Putri Mahenu; Birgita Elsia Setiarini; Familia Putri Wulandari; Fransisca Wahyu Indriastuti Indriastuti; Klemen Wahyu Kurniadi; Florentinus Dika Octa Riswanto (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2018)
The limitations of science and students' awareness of reproductive health causes such students susceptible to various diseases caused by viruses, fungi, or bacteria. This program aims to provide education about "Reproductive Health for Students in Yaketunis Yogyakarta through the media “Pakem Braille", and examples of diseases that can be caused due to lack of maintaining health and hygiene of reproductive organs. The program is expected to increase interest in learning, especially science and awareness of students of MTs Yaketunis in maintaining reproductive health, producing the media "Pakem Braille" and learning modules, and also an article publication. The method used in educational activities consisted of a lecture with and without the media "Pakem Braille", where the media will be used as props in the educational process. Overall the students' understanding regarding the material of reproductive health in humans increased by 77.78%. Students’ interest also increased, it is seen from the increase in the number of questions asked by students amounted to 61.11%. Knowledge and awareness of reproductive health-related students increased to 73% and the result obtained was 55.6% of students categorized as having sufficient awareness and 38.9% of students considered to have good awareness of the importance of maintaining reproductive health.